Bone morphogenetic protein‐2 enhances gonadotropin‐independent follicular development via sphingosine kinase 1. (25th November 2020) - Ito, Masami; Yoshino, Osamu; Ono, Yosuke; Yamaki‐Ushijima, Akemi; Tanaka, Tomoko; Shima, Tomoko; Orisaka, Makoto; Iwase, Akira; Nakashima, Akitoshi; Saito, Shigeru
Abstract: Problem: Pre‐ovulatory mature follicles are not readily induced from gonadotropin (Gn)‐independent early follicles in the poor ovarian response (POR) state, characterized by reduced number of retrieved oocytes. Bone morphogenetic protein (BMP), which is expressed in the ovary, contributes to early folliculogenesis, but its precise underlying mechanism remains unknown. The purpose of this study was to examine the effects of BMP‐2 on granulosa cells (GCs) of Gn‐independent early follicles. Method of study: Sphingosine kinase 1 (SPHK1) localization, which produces sphingosine 1‐phosphate (S1P), was examined in human early follicles by immunohistochemistry. SPHK1 mRNA levels were examined in Gn‐independent bovine GCs (bGCs) and human nonluteinized granulosa cell line (HGrC1) cells. Phosphorylated Yes‐associated protein (YAP) expression was evaluated by Western blot, and its localization was evaluated immunocytochemically in bGCs. Verteporfin, a selective YAP inhibitor, was used to explore the influence of YAP on BMP‐2‐induced bGCs proliferation. Results: The expression of SPHK1 was observed in human GCs of primary and secondary follicles. BMP‐2 significantly induced SPHK1 mRNA expression in bGCs and HGrC1 cells. Both BMP‐2 and S1P decreased phosphorylated YAP protein levels and induced the nuclear translocation of YAP significantly, thereby increasing the number of bGCs by suppressing the Hippo pathway. This BMP‐2‐induced cell proliferation was completely blocked by verteporfin. Conclusion: This is a first report showing that BMP‐2 up‐regulated SPHK1 mRNA expression in GCs and promoted GCs proliferation through Hippo pathway suppression. Thus, BMP‐2 contributes to Gn‐independent folliculogenesis via SPHK1, suggesting a potential therapeutic strategy for the POR patients with follicular dysgenesis.